The Influence of Hedonic Shopping Motivation and Store Atmosphere on Impulsive Buying at Transmart in Surabaya City - Yuda Susanto; Siti Aminah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to evaluate the impact of hedonic shopping motivation and store atmosphere on impulsive buying in Transmart Surabaya City. The mthod applied in this study is a quantitative approach with the use of pursosive sampling techniques. The research sample consisted of 110 respondents who had visited Transmart Surabaya City. Data for this study was collected through filling oute questionnaires that were distributed to these visitors. Data analysis using the Partial Least Square (PLS) model. The findings of this study show that hedonic shopping motivation has a significant influence on impulsive buying to Surabaya City Transmart visitors and store atmosphere does not have a significant influence on impulsive buying to Surabaya City Transmart visitors.